Investigação da suscetibilidade à anfotericina B e à miltefosina em isolados clínicos de "Leishmania" spp. : estudos "in vitro" e "in vivo" = Investigation of susceptibility to amphotericin B and miltefosine in clinical isolates of "Leishmania" spp.: "in vitro" and "in vivo" studies - Ferreira, Bianca Alves, 1997- (2022)
Orientador: Adriano Cappellazzo Coelho